Swift 4 for Absolute Beginners Develop Apps for iOS - Kaczmarek, Stefan (Apress, 2018)
Stay motivated and overcome obstacles while learning to use Swift Playgrounds to be a great iOS developer. This book is perfect for those with no programming background, those with some programming experience but no object-oriented experience, or those that have a great idea for an app but haven't programmed since school, and it is now updated for Swift 4. Many people have a difficult time believing they can learn to write iOS apps. Swift 4 for Absolute Beginners, along with the free, live online training sessions will show you how to do so. You'll learn Object Oriented Programming and be introduced to HealthKit before moving on to write your own iPhone and Watch apps from scratch. Gary Bennett and Brad Lees are full-time professional iOS developers and have developed a broad spectrum of apps for Fortune 500 companies. The authors have taken their combined 14 years of writing apps, teaching online iOS courses, the experience from their first three iOS books, along with their online instruction and free online forum at XcelMe.com to create an excellent training book.